Relationship Between Factors Affecting ICT Integration and Level of JHS Teachers Understanding on ICT in Zamboanga City - A. Mendoza, Lourdes (International Journal of Scientific Research and Management (IJSRM), 2022)
The study aims to identify the factors affecting the integration of ICT and the level of understanding among JHS Teachers in select National High School in Zamboanga City for school year 2021-2022. The study utilized the Descriptive Quantitative Correlational Design and revealed, the relationship between the factors affecting ICT integration and level of understanding of teachers in select JHS in Zamboanga City was moderately correlated, and can be seen, that the factors such as availabiltity of resources, teacher competencies and the relevant training attended, revealed to be moderately affected, moderately influenced the teachers’ level of understanding on ICTs integration in the teaching-learning process, in terms of microsoft office and internet apps.